Redistributing risk management responsibilities to achieve the Sustainable Development Goal (SDG) for safely-managed drinking water in rural Bangladesh (REACH Policy paper) - Fischer, A; Hope, R; Hoque, S; Hakim, A; Alam, MM (University of Oxford, 2020)
The drinking water sector is off track to reach Sustainable Development Goal (SDG) 6.1 with over a quarter of the world’s population lacking safe and reliable services. Policy approaches are shifting away from provision of access towards managing the multiple risks of water supply and quality. A recent article published in Global Environmental Change considered how infrastructure, information, and institutional systems evolved in Bangladesh. It identified the unintentional consequences of reallocating management responsibility for rural water services away from government agencies towards individuals and households. This policy paper provides a summary of the policy context and recommendations to recognize the increased risks facing an unregulated and unmonitored self-supply rural water service model.